A matemática financeira na sala de aula. Uma proposta de atividades com problemas do cotidiano - Pavani, Vinícius Vaz (Universidade Federal de São Carlos, 2018)
In this research we present the idealization, the construction, the application and the analysis of results of a didactic sequence to the teaching and the resumption of some mathematical contents, having as a guide financial mathematics applied on a daily basis. As a final product we got four activities sheets with items (questions) of gradual complexities to enable the student`s autonomy and facilitate understanding in relation to the proposed situations. The activities sheets were applied in two classes of the third grade of the Industrial Automation Technical Course and Computer Technical Course for Internet, both integrated to High School in 2017 at Instituto Federal do Paraná campus in Telêmaco Borba-PR.
Keywords: Matemática financeira; Juros; Porcentagem; Investimento; Fichas de atividades; Financial mathematics; Interests; Percentage; Investment; Activities sheets; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA